Effects of Covid-19 on Tourism in Lumbini Province of Nepal - Gautam, Subas (Academia Research Journal, 2023)
This research article aims to assess the impact of the COVID-19 pandemic on the tourism sector in four districts of Lumbini Province, Nepal, namely Banke, Bardiya, Dang, and East Rukum. The COVID-19 outbreak, which originated in Wuhan, China in December 2019, rapidly spread worldwide, affecting people of all ages, with greater severity observed among the elderly and those with chronic health conditions. Declared a pandemic by the World Health Organization (WHO) in March 2020, the COVID-19 crisis has brought uncertainty and has significantly impacted various sectors of human life, including the economic, political, social, and cultural aspects. Given the relevance of measuring the pandemic’s impact, this study primarily focuses on the economic consequences in the tourism sector. Specific objectives include examining the effects on tourist arrivals, the income of entrepreneurs, and the level of employment in the selected districts. However, the study acknowledges certain limitations, such as its exclusive focus on only four districts of Lumbini Province, limiting generalization to the entire nation. Additionally, it solely examines the economic impact of COVID-19, excluding other potential impacts related to social, behavioral, and cultural aspects. To collect data for the research, quantitative methodologies and statistical software were utilized, gathering primary data from various tourism-related establishments such as hotels, restaurants, cottages, grocery stores, and trekking companies. The study emphasizes the importance of early-stage exploratory research to better understand the economic impact of the pandemic on the tourism industry in the selected regions.